x(x -3) = 88 Solve for x.?

please can any one answer

7 Answers

Relevance
  • Favorite Answer

    x(x - 3) = 88

    x² - 3x – 88 =0

    x² - 11x + 8x – 88 = 0

    x(x – 11) + 8(x – 11) = 0

    (x – 11)(x + 8) = 0

    So, x – 11 = 0 or x + 8 = 0

    Hence, x = 11 or x = -8

  • 9 years ago

    x^2-3x=88

    x^2-3x-88=0

    then u must find the sum product and the factor

    sum= -3

    product u do -88*1...1 at x^2

    factor= -11, 8..

    then it becomes like this,,,

    (x + 8) (x - 11)=0

    x= -8 or x= 11...

    for the factor here it is

    u take the factors and u add them and see if u get the sum...

    and u multiply the factor to see if u get the product..

    so simple

    i hope it helps....

    and instead of writing the full form of sum and all u can just write s, p and f...and u can do the s,p,f in your margin..so as not to disturb the equation

    thank you..

  • 9 years ago

    Hey Ishan

    first open the brackets and get x^2-3x=88

    you have formed a quadratic equation by that

    x^2-3x-88=0

    use either quadratic formula or completing the square to solve this

    you will find that x=11 or x=-8

    hope you have understood

    good luck!

  • 9 years ago

    x(x - 3) = 88

    x² - 3x = 88

    x² - 3x - 88 = 0

    { x² - 3x } - 88 = 0

    { [x - (3/2)]² - (9/4) } - 88 = 0

    [x - (3/2)]² - (9/4) - 88 = 0

    [x - (3/2)]² - (9/4) - (352/4) = 0

    [x - (3/2)]² - [(9 + 352)/4] = 0

    [x - (3/2)]² - (361/4) = 0

    [x - (3/2)]² - (19/2)² = 0 → identity : a² - b² = (a + b)(a - b)

    [x - (3/2) + (19/2)] * [x - (3/2) - (19/2)] = 0

    [x + (19 - 3)/2] * [x - (19 + 3)/2] = 0

    (x + 8)(x - 11) = 0

    Solution : S = { - 8 ; 11 }

  • How do you think about the answers? You can sign in to vote the answer.
  • DOVE
    Lv 6
    9 years ago

    x(x -3) = 88

    x^2 -3x = 88

    x^2 -3x - 88=0

    (x+8)(x-11)=0

    x= -8 or x=11

  • ?
    Lv 4
    9 years ago

    x2 - 3x - 88 = 0

    a=1; b=-3; c=-88

    D= b2 - 4ac = 9 - 4*1* (-88)= 9 + 352 = 361

    x(1) = (-b + squareroot 361)/2a = (3+ 19)/2*1 = 22/2= 11

    x(2) = (-b - squareroot 361)/2a = (3 - 19)/2*1 = -16/2= -8

  • Anonymous
    9 years ago

    x=11 or x=-8

Still have questions? Get your answers by asking now.